2008
DOI: 10.1007/bf03346388
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of hyperprolactinemia: Results of a Brazilian multicenter study with 1234 patients

Abstract: Prolactinomas, drug induced hyperprolactinemia, and macroprolactinemia were the 3 most common causes of hyperprolactinemia. Although PRL levels could not reliably define the etiology of hyperprolactinemia, PRL values >500 ng/ml were exclusively seen in patients with prolactinomas. CAB was significantly more effective than BCR in terms of prolactin normalization, tumor shrinkage, and tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 36 publications
6
94
0
5
Order By: Relevance
“…Clinical evidence indicates that hyperprolactinemia is a frequent cause of reproductive dysfunction and may lead to infertility in males and females (10)(11)(12)(13). Pathological hyperprolactinemia is mainly caused by the presence of a prolactinoma or is due to pharmacological effects induced by drugs that interact with the dopamine system.…”
mentioning
confidence: 99%
“…Clinical evidence indicates that hyperprolactinemia is a frequent cause of reproductive dysfunction and may lead to infertility in males and females (10)(11)(12)(13). Pathological hyperprolactinemia is mainly caused by the presence of a prolactinoma or is due to pharmacological effects induced by drugs that interact with the dopamine system.…”
mentioning
confidence: 99%
“…As mentioned earlier, 9%-30% of metastases detected by re-examining the lymph nodes with serial sections could not be detected in routine pathologic infertility testing (10,41) This insufficiency could be removed by reducing the cross-sectional area from the lymph node and by cytokeratin immunohistochemical staining (i.e., specific monoclonal antibody) (41, 42). A learning curve (19,32) was reported in many related studies. An experienced surgeon who applied both methods together had an SLN detection rate of 94%, whereas this rate was 86% for newly recruited surgeons (43).…”
Section: Discussionmentioning
confidence: 86%
“…In the National Surgical Adjuvant Breast and Bowel Project (NSABBP)-B04 study, the average number of lymph nodes removed was between 7 and 30 at different centers. This huge difference between the numbers was based on the surgical technique applied, the experience and tendency of the surgeon, and the ability of the pathologist to evaluate the dissection material (18,19,20,21). In the present study, the number of lymph nodes removed in 44 patients who underwent axillary dissection detected using the ISB method was minimum 7 and maximum 23 (average number 14.2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrate that risperidone can increase PRL levels by more than 200 ng/mL; however, PRL levels in drug-associated hyperprolactinemia are generally in the range of 25-100 ng/mL (18). A study has shown that antidepressants (tricyclic antidepressants) and antipsychotics (haloperidol, phenothiazines, and risperidone) are responsible for the majority of cases with drug-associated hyperprolactinemia (19). Serum PRL level increases within hours after antipsychotic use and returns to normal within 2-4 days after discontinuation of chronic therapy (20).…”
Section: Pharmacological Causesmentioning
confidence: 99%